The Tweedles go online - Kulling, Monica (Groundwood Books, 2015)
When their neighbors the Hamms announce that they've "gone online" by buying a telephone, Mama excitedly follows suit. But will the lure of the telephone be too much of a distraction for this sweetly old-fashioned family? Fresh from their adventure with their new electric car, Mama decides that the family needs a telephone to keep up with the changing times, and daughter Frances could not be more thrilled. But not all the Tweedles are convinced. Son Francis only has eyes for the family's car, and Papa worries about the family's privacy. Once the phone is installed in the family's home, they can hardly believe the noise it makes! But Frances takes a shine to the telephone immediately, and her enthusiasm for the new device threatens to keep the whole family up at night. Will the Tweedles ever be able to go offline again? This clever companion to The Tweedles Go Electric gently pokes fun at our modern addiction to technology, while further endearing readers to the sweetly odd Tweedles family.